Co‐ablation versus cryoablation for the treatment of stage III–IV non‐small cell lung cancer: A prospective, noninferiority, randomized, controlled trial (RCT). Issue 4 (14th December 2020) - Yang, Wuwei; An, Yonghui; Li, Quanwang; Liu, Chuanbo; Zhu, Baorang; Huang, Qianfu; Zhao, Mengfei; Yang, Fei; Feng, Huasong; Hu, Kaiwen
Abstract: Background: This study compared a co‐ablation (CA) system, which is a novel ablation device, with an argon‐helium cryoablation (AHC) system. We aimed to compare the efficacy and safety of CA and AHC for the treatment of stage III–IV non‐small cell lung cancer (NSCLC). Methods: We conducted a multicenter randomized controlled trial (RCT) to determine whether CA was noninferior to AHC. The primary efficacy endpoints were the iceball coverage rate (ICR) and the disease control rate (DCR) one month after treatment. Noninferiority was declared if the lower limit of two‐sided 95% confidence interval (CI) was less than 10%. The ICR and DCR were identified by logistic regression. Treatment safety was assessed. Results: A total of 81 patients underwent randomization (41 assigned to the CA and 40 assigned to the AHC groups)and transthoracic ablation. The ICRs in the CA and AHC groups were 99.24% ± 2.18% and 98.66% ± 3.79%, respectively. Central lesions were associated with an increased risk of an incomplete ICR. The DCRs in the CA and AHC groups were 97.6% and 95%, respectively. A smaller lesion area in the CA group was significantly correlated with a better DCR. The rate of complications was 29.26% in the CA group and 30% in the AHC group. ( P = 0.943). There was less probe usage per patient in the CA group. Conclusions: We determined that CA is noninferior to AHC in terms of efficacy and safety for the treatment of stage III–IV NSCLC. A smaller lesion area in the CA group was significantly correlated with a better DCR. Key points: CA was noninferior to AHC for stage III–IV NSCLC. Abstract : Co‐ablation (CA) is noninferior to argon‐helium cryoablation (AHC) in terms of efficacy and safety for the treatment of stage III–IV NSCLC. A smaller lesion area in the CA group was significantly correlated with a better disease control rate (DCR).